Risk Factors for COVID-19 Deaths Among Elderly Nursing Home Medicare Beneficiaries in the Prevaccine Period. (7th October 2021) - Lu, Yun; Jiao, Yixin; Graham, David J; Wu, Yue; Wang, Jing; Menis, Mikhail; Chillarige, Yoganand; Wernecke, Michael; Kelman, Jeffrey; Forshee, Richard A; Izurieta, Hector S
Abstract: Background: We evaluated prevaccine pandemic period COVID-19 death risk factors among nursing home (NH) residents. Methods: In a retrospective cohort study covering Medicare fee-for-service beneficiaries aged ≥65 years residing in US NHs, we estimated adjusted hazard ratios (HRs) using multivariate Cox proportional hazards regressions. Results: Among 608251 elderly NH residents, 57398 (9.4%) died of COVID-19–related illness 1 April to 22 December 2020; 46.9% (26893) of these deaths occurred without prior COVID-19 hospitalizations. We observed a consistently increasing age trend for COVID-19 deaths. Racial/ethnic minorities shared similarly high risk of NH COVID-19 deaths with whites. NH facility characteristics for-profit ownership and low health inspection ratings were associated with higher death risk. Resident characteristics (male [HR, 1.69], end-stage renal disease [HR, 1.42], cognitive impairment [HR, 1.34], and immunocompromised status [HR, 1.20]) were death risk factors. Other individual-level characteristics were less predictive of death than in community-dwelling population. Conclusions: Low NH health inspection ratings and private ownership contributed to COVID-19 death risks. Nearly half of NH COVID-19 deaths occurred without prior COVID-19 hospitalization and older residents were less likely to get hospitalized with COVID-19. No substantial differences were observed by race/ethnicity and socioeconomic status for NH COVID-19 deaths. Abstract : Within nursing homes, low health inspection ratings and private ownership type contributed to COVID-19 deaths among elderly residents after adjusting for individual characteristics. No substantial differences were observed by race/ethnicity and socioeconomic status for COVID-19 deaths.